2015
DOI: 10.4209/aaqr.2015.01.0039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Fate, and Re-Suspension of Aerosol Particles (0.3-10 µm): The Effects of Occupancy and Carpet Use

Abstract: In this study we present the particle number size distribution (diameter 0.3-10 µm with 1-minute time resolution) inside four offices (naturally ventilated) inside two university buildings. Each office had a typical environment in terms of occupancy and furniture. We focused on the differences between workdays and weekends in terms of particle number (PN) and particle mass (PM, assuming spherical particles with unit density) concentrations. Moreover, we illustrated the effect of workers' activity (occupancy, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…This agree well with observation of Thatcher and Layton (1995), Abt et al (2000) and Hussein et al (2015a) who found that movement in the indoor environment significantly . Practically constant value for PM 0.7-10 observed during all season indicates also stable regime of visits.…”
Section: Estimation Of Visitors Influencesupporting
confidence: 82%
“…This agree well with observation of Thatcher and Layton (1995), Abt et al (2000) and Hussein et al (2015a) who found that movement in the indoor environment significantly . Practically constant value for PM 0.7-10 observed during all season indicates also stable regime of visits.…”
Section: Estimation Of Visitors Influencesupporting
confidence: 82%
“…Evaluation of indoor air pollution and concentrations of particulate and gaseous indoor air pollutants in Middle Eastern dwellings has been given limited attention in the literature. In Jordan, one study investigated the effects of indoor air pollutants on the health of Jordanian women [29] and three studies evaluated concentrations of indoor particles in Jordanian indoor environments [30][31][32]. These studies provided useful insights on the extent of air pollution in selected Jordanian indoor environments and the role of cultural practices on the nature of indoor emission sources.…”
Section: Introductionmentioning
confidence: 99%
“…The problem not only concerns atmospheric pollution, but also the indoor environment since people in industrial nations spend most of their time inside buildings . Indoor air can be deteriorated either by infiltration from outside, by indoor sources such as, e.g., smoking, cooking or candles or due to resuspension by cleaning or walking .…”
Section: Introductionmentioning
confidence: 99%